Quercetin Bioavailability Evaluation on Standardized Herbal Medicine Containing Guava Leaf Extract with HPLC - Yulion, Rizky; Yulianis, Yulianis; Suntri, Suntri (Biology, Medicine, & Natural Product Chemistry, 2023)
Standardized herbal medicines are classified as one of Indonesia's natural medicine ingredients in addition to herbal medicine and phytopharmaceuticals. The safety and efficacy of standardized herbal medicines are scientifically proven through preclinical trials, and raw materials and products have been standardized. One includes standardized herbal medicines is diapet, psidii, lelap, fitolac, and glucogarp. To determine the bioavailability of standardized herbal products containing guava leaf extract (Psidium guajava L.). which uses single and combined natural materials. The method used is experimental with a crossover design. Blood samples are taken from the marginalis vein of the rabbit ear at 0.5 hours; 1; 2; 4; and 6. The level of quercetin in the blood is determined by the reverse-phase HPLC method. The mobile phase used is methanol:aquabidest (59:41,v/v), stationary phase octadecyl silica (C18), flow rate 1 mL/min, UV-Vis detector 370 nm, and injection volume 20 ?L. The value of bioavailability parameters obtained in the parameters Cpmax, Tmax, and AUC of product A is 1.486454 ?g / ml; 1.4 hours and 10.2615291 ?g/ml/h, product B is 1.29224019 ?g/ml; 1.5 hours and 11.30810501 ?g/ml/hour. Based on the results of this study, it can be concluded that the bioavailability profile of the two products is not much different, so it is expected that the effects caused are the same.